PENGARUH MENDENGARKAN ASMAUL HUSNA TERHADAP MUAL MUNTAH PADA IBU HAMIL - Nur Rakhmawati (Jurnal Keperawatan Malang, 2020)
Background: Pregnancy affects the body's system, both hormonally, physically, and psychologically. Nausea that is sometimes accompanied by vomiting usually arises from the age of 5 weeks, which is calculated based on the first day at the last and reaches the peak at 8 weeks to 12 weeks and ends at 16 to 18 weeks. Nausea and vomiting in pregnancy is the reaction of the pregnant woman's body to changes that occur as a result of pregnancy. Objective: This study is to find out the effect of asmaul husna therapy on vomiting nausea in pregnant women. Methods: This research was conducted on 16 respondents using quasy experiment research method with Pre Test and Post Test Without Control Group approach. Sampling is done on a non probability sampling with purposive sampling technique. Data analysis in this study using wilcoxon test. The population of this study is pregnant women total 16 respondents. Results: There is therapy listening to Asmaul Husna terhadap nausea vomiting in pregnant women is p value of 0,000 < 0.0. Conclusion: This study is the effect of Asmaul Husna listening therapy on vomiting nausea in pregnant women.